The Relationship between Self-Concept and the Anxiety Level of Prisoners in Class II.A Penitentiary in Bulukumba - Fatmawati; Nurlina; Ira Puspasari (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Based on the results of routine examinations from clinic officers in correctional institutions found 20 people out of 178 suffer from mild anxiety levels, while 10 people. and 121 inmates 15% of prisoners have anxiety with a moderate anxiety level of 13 people. Looking at the phenomena based on interviews with 5 prisoners in Class II.A Penitentiary Institution. Bulukumba on February 2, 2017, stated that prisoners in Class II Penitentiary Bulukumba claimed to experience feeling depressed, beaten and disappointed at the beginning of their lives inside a prison. The purpose of this study is to determine the relationship of self-concept with the level of anxiety of prisoners in Class II. A Penitentiary. Bulukumba. This study uses an analytic observational design with a